Finite element modeling of nano porous sintered silver material using computed tomography images. Issue 5 (9th May 2019) - Meyghani, B.; Awang, M.; Bokam, P.; Plank, B.; Heinzl, C.; Siow, K. S.
Abstract: Limitations in the packaging industry require improvements in lead‐based microelectronics, because regulations restricting hazardous substances have ended the use of conventional lead‐based solders. Sintered silver paste presents an alternative method for bonding chips to a substrate because it has low sensitivity to the oxidation, high melting point, and improved thermal and electrical conductivity. Due to the sintering process, however, the silver exhibits a significant pore fraction that substantially reduces the density of the material compared to bulk silver. The traits of the sintered silver pastes are affected by the pore distribution; hence, it can be considered as a significant factor in modelling the behaviour of the whole electronic system under operating conditions. This study defines the influence of the morphology and pore distribution on the response of the silver material. The quality of tomographic images was improved through coding a program in MATLAB®. Finite element software ABAQUS® was employed to evaluate the elastic properties of the material. To validate the model, the results have gone through several studies to determine changes of the material properties. Translation abstract: Einschränkungen in der Verpackungsindustrie erfordern Verbesserungen in der Mikroelektronik auf Bleibasis, da Vorschriften, die gefährliche Substanzen einschränken, den Einsatz herkömmlicher Lote auf Bleibasis nicht mehr gestatten. Eine gesinterte Silberpaste ist eine Alternative zum Verbinden von Chips mit einem Substrat, da es eine geringe Oxidationsempfindlichkeit, einen hohen Schmelzpunkt und eine verbesserte thermische und elektrische Leitfähigkeit aufweist. Aufgrund des Sinterprozesses zeigt das Silber jedoch einen signifikanten Porenanteil, der die Dichte des Materials im Vergleich zu klassischem Silber erheblich verringert. Die Eigenschaften der gesinterten Silberpasten werden durch die Porenverteilung beeinflusst. Daher kann dieser als wesentlicher Faktor bei der Modellierung des Verhaltens des gesamten elektronischen Systems unter Betriebsbedingungen betrachtet werden. Diese Studie definiert den Einfluss der Morphologie und der Porenverteilung auf die Reaktion des Silbermaterials. Die Qualität der Tomographiebilder wurde durch ein in MATLAB® erstelltes Programm verbessert. Die Finite‐Elemente‐Software ABAQUS® wurde zur Bewertung der elastischen Eigenschaften des Materials eingesetzt. Zur Validierung des Modells wurden die Ergebnisse in mehreren Studien untersucht, um Änderungen der Materialeigenschaften zu ermitteln.